Reaching Perinatal Women Online: The Healthy You, Healthy Baby Website and App - Lydia Hearn; Margaret Miller; Leanne Lester (Journal of Obesity)
Overwhelming evidence reveals the close link between unwarranted weight gain among childbearing women and childhood adiposity. Yet current barriers limit the capacity of perinatal health care providers (PHCPs) to offer healthy lifestyle counselling. In response, today’s Internet savvy women are turning to online resources to access health information, with the potential of revolutionising health services by enabling PHCPs to guide women to appropriate online resources. This paper presents the findings of a project designed to develop an online resource to promote healthy lifestyles during the perinatal period. The methodology involved focus groups and interviews with perinatal women and PHCPs to determine what online information was needed, in what form, and how best it should be presented. The outcome was the development of the Healthy You, Healthy Baby website and smartphone app. This clinically-endorsed, interactive online resource provides perinatal women with a personalised tool to track their weight, diet, physical activity, emotional wellbeing, and sleep patterns based on the developmental stage of their child with links to quality-assured information. One year since the launch of the online resource, data indicates it provides a low-cost intervention delivered across most geographic and socioeconomic strata without additional demands on health service staff.